Development of an android-based educational game to improve junior high school students’ mathematical numeracy skills - Adrillian, Hendrisa; Mariani, Scolastika; Prabowo, Ardhi (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose:  This research aims to develop learning media that is assisted by Android-based educational game is valid, practical, and effective for improving mathematical numeracy skills.Method: The flow utilized is the multimedia development life cycle, which consists of concept, design, obtaining context material, assembly, testing, and distribution. The validity of the media is proven through evaluations by media, material, and instructional module experts, while practicality is shown through the students’ reaction questionnaires.Findings: The validity results were obtained by media experts 0,92 (very high); material experts 0,913 (very high); and instructional module experts 0,8615 (very high). Then, the results of the student reaction questionnaire obtained a percentage of 83% with good criteria. Meanwhile, the results of effectiveness are explained by the right party t-test obtained , then  was rejected.Significance: The research results demonstrate that developing learning media assisted by an Android-based educational game is valid, practical, and effective for improving mathematical numeracy skills and it has the potential to be utilized as an alternative learning media to support mathematics instruction in schools.